CLEAR ALIGNER ORTHODONTICS AND PERIODONTAL HEALTH: A CLINICAL, MICROBIOLOGICAL AND RADIOLOGICAL ASSESSMENT OF SAFETY AND EFFECTIVENESS IN ADULT PATIENTS (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Clear aligner orthodontics has become increasingly popular among adult patients due to its aesthetic advantages, removability, and improved oral hygiene maintenance compared with fixed appliances. However, the impact of aligners on periodontal tissues, oral microbiota, and alveolar bone requires comprehensive evaluation.The aim of this study was to assess the safety and effectiveness of clear aligner therapy in adult patients using clinical, microbiological, and radiological parameters.Adult patients with moderate malocclusions and healthy periodontal conditions were examined. The assessment included clinical periodontal indices, PCR-based analysis of periodontal pathogens, and radiological evaluation using panoramic radiography and cone-beam computed tomography (CBCT).The results demonstrated that clear aligner therapy does not negatively affect periodontal health when adequate oral hygiene is maintained. Microbiological changes observed during the initial stages of treatment were transient and not associated with clinical inflammation. Radiological findings confirmed the absence of pathological alveolar bone resorption and the predictability of orthodontic tooth movement.Clear aligner therapy can be considered a safe and effective orthodontic treatment option for adults with preserved periodontal health.